PEMANFATAN EKONOMI DIGITAL DALAM PEMASARAN PRODUCK BUCKET BUNGA : STUDI KASUS BRAND PIDY.FLORIST - tomi, tomi; Umi, Umi Safrilia Lestari; Syahru, Muhammad Syahru Ramdhan (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2025)
This study aims to examine the use of the digital economy in marketing flower bucket products through a case study of the Pidy.florist brand. With the development of digital technology, businesses are increasingly encouraged to utilize online platforms such as Instagram and WhatsApp to expand market reach and increase sales. This study uses a qualitative approach with a case study method to understand the digital marketing strategy implemented by Pidy.florist. The results show that utilizing social media as a primary promotional tool, utilizing marketplaces for more secure transactions, and intensive communication through messaging apps can increase brand visibility and customer loyalty. This study also reveals challenges faced, such as intense competition and changes in social media algorithms. These findings are expected to contribute to the development of digital marketing strategies for small and medium enterprises (SMEs) in the digital economy era. Keywords: Digital economy, Marketing, Online Shop, MSE